Effects of mindfulness training on the default mode network in borderline personality disorder. (25th June 2019) - Carmona i Farrés, Cristina; Elices, Matilde; Soler, Joaquim; Domínguez‐Clavé, Elisabet; Martín‐Blanco, Ana; Pomarol‐Clotet, Edith; Salvador, Raymond; Martinez‐Horta, Saül; Pascual, Juan C.
Abstract: Patients with borderline personality disorder (BPD) present dysfunctions of the default mode network (DMN). Mindfulness training has proven effective to improve the symptoms of BPD. The present study examines the effect of mindfulness training on BPD symptomatology and DMN activity during the performance of a working memory task in patients with BPD. Sixty‐five individuals with BPD were randomized to receive psychotherapy with either the mindfulness module of dialectical behavioural therapy (DBT‐M) or with interpersonal effectiveness module (DBT‐IE). The impact of treatments was evaluated with clinical and mindfulness variables as well as with functional magnetic resonance imaging during performance of the task. Both groups showed improvement in BPD symptoms and other clinical variables after treatment. Unexpectedly, there were no between‐group differences in DMN activation or deactivation. However, activation of the left anterior insula increased in both groups after the intervention. Compared with the control group, participants in the DBT‐M group presented higher deactivation in a cluster extending bilaterally from the calcarine to the cuneus and superior occipital gyri.